A label-free electrochemical aptasensor based on the core–shell Cu-MOF@TpBD hybrid nanoarchitecture for the sensitive detection of PDGF-BB. Issue 3 (8th December 2020) - Li, Ya; Liu, Zhiling; Lu, Wenbo; Zhao, Man; Xiao, He; Hu, Tianjun; Ma, Jianchun; Zheng, Zhanfeng; Jia, Jianfeng; Wu, Haishun
Abstract : A novel label-free electrochemical aptasensor based on core–shell Cu-MOF@TpBD hybrid nanocomposites has been prepared for the sensitive detection of PDGF-BB. Abstract : As one of the significant serum cytokines, platelet-derived growth factor-BB (PDGF-BB) is a crucial protein biomarker overexpressed in human life-threatening tumors, the sensitive identification and quantification of which are urgently desired but challenging. Herein we report a novel core–shell nanoarchitecture consisting of Cu-based metal–organic frameworks (Cu-MOFs) and covalent organic frameworks (denoted as TpBD-COFs), which was used to prepare an aptasensor for the detection of platelet-derived growth factor-BB (PDGF-BB). The central Cu-MOFs function as signal labels with no need for extra redox media, whereas the porous TpBD serves as the shell to immobilize the PDGF-BB-targeted aptamer strands in abundance via strong interactions involving π–π stacking, electrostatic, and hydrogen bonding interactions. The proposed aptasensor based on Cu-MOF@TpBD can achieve a detection limit as low as 0.034 pg mL −1 within the dynamic detection range from 0.0001 to 60 ng mL −1 . The hybridization of MOFs and COFs, together with the immobilization with the specific analyte targeted aptamer, provides a promising and propagable approach to prepare an aptasensor for the simple, sensitive, and selective detection of a specific biomarker in clinical diagnosis.